2012
DOI: 10.1371/journal.pone.0041308
|View full text |Cite
|
Sign up to set email alerts
|

Resource Use and Costs Associated with Coeliac Disease before and after Diagnosis in 3,646 Cases: Results of a UK Primary Care Database Analysis

Abstract: BackgroundDespite the considerable health impact of coeliac disease (CD), reliable estimates of the impact of diagnosis on health care use and costs are lacking.AimsTo quantify the volume, type and costs, in a United Kingdom primary care setting, of healthcare resources used by individuals diagnosed with CD up to ten years before and after diagnosis, and to estimate medical costs associated with CD.MethodsA cohort of 3,646 CD cases and a parallel cohort of 32,973 matched controls, extracted from the General Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 38 publications
1
30
0
1
Order By: Relevance
“…CPRD records listing administrative staff, such as secretaries, IT staff, practice and fund managers and receptionists, were not counted as a clinical direct contact with the patient and were, therefore, excluded from the costs. Following a previous study, 142 we only counted one consultation per day if more than one was recorded per patient. Primary care contacts and tests were costed using unit costs from national cost databases (Table 17).…”
Section: Primary Care Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…CPRD records listing administrative staff, such as secretaries, IT staff, practice and fund managers and receptionists, were not counted as a clinical direct contact with the patient and were, therefore, excluded from the costs. Following a previous study, 142 we only counted one consultation per day if more than one was recorded per patient. Primary care contacts and tests were costed using unit costs from national cost databases (Table 17).…”
Section: Primary Care Costsmentioning
confidence: 99%
“…Following a previous study, 142 we counted only one consultation per day. Pharmaceuticals were costed using the number of prescriptions stratified by BNF code 90 per patient.…”
mentioning
confidence: 99%
“…Because of the low cost for simple, commonly used tests like lipid panels and complete blood counts, we elected to ignore these costs. However, others have included test costs, and the methods for these are provided in several studies 13,16 . They generally involve identifying the Read codes for relevant tests, and identifying the appropriate NHS cost for each.…”
Section: Estimating Costs In Hyperlipidemia Patients In the Ukmentioning
confidence: 99%
“…As a result of these resources, a variety of studies have been conducted that estimate costs based on resource utilization derived from CPRD and HES data, many of which were published recently [7][8][9][10][11][12][13][14][15][16][17][18] . However, it is still challenging to understand the methods used, and to implement them in research 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that gluten-free food is not always readily available, and it is considerably more expensive than regular, gluten-containing foods [8]. The increasing incidence of celiac disease in the population has negative effects not only on the quality of life but also on the health care system: it has been estimated that the average annual health care costs per-patient in primary care significantly increased by 91% for CD patients after they had been diagnosed with the disease [9]. The impact is also evident for the agricultural and food sectors: wheat is one of the first three cereals for diffusion and cultivation for human nutrition.…”
Section: Introductionmentioning
confidence: 99%